A Contrastive Analysis Between English And Indonesian Noun Suffixes In The Hortatory Text - Renova S. Hutasoit; Risma Sitinjak; Gracela Situmorang; Anita Sitanggang (PIJAR: Jurnal Pendidikan dan Pengajaran, 2023)
The purpose of this study is to describe and analyze the contrast between English and Indonesian noun suffixes in hortatory texts. It investigates the linguistic patterns and semantic nuances conveyed by these suffixes in both languages. Through comparative analysis of hortatory texts. This research method uses qualitative literature study. This study highlights how the choice of noun endings influences the persuasive impact and rhetorical strategies used in each language. These findings contribute to a deeper understanding of cross-linguistic variation in hortatory discourse, offering valuable insights for language learners and educators